Direct costs of asthma in Brazil: a comparison between controlled and uncontrolled asthmatic patients - Santos,L.A. (2007)
Asthma is a common chronic illness that imposes a heavy burden on all aspects of the patient's life, including personal and health care cost expenditures. To analyze the direct cost associated to uncontrolled asthma patients, a cross-sectional study was conducted to determine costs related to patients with uncontrolled and controlled asthma. Uncontrolled patient was defined by daytime symptoms more than twice a week or nocturnal symptoms during two consecutive nights or any limitations of activities, or need for relief rescue medication more than twice a week, and an ACQ score less than 2 points. A questionnaire about direct cost stratification in health services, including emergency room visits, hospitalization, ambulatory visits, and asthma medications prescribed, was applied. Ninety asthma patients were enrolled (45 uncontrolled/45 controlled). Uncontrolled asthmatics accounted for higher health care expenditures than controlled patients, US$125.45 and US$15.58, respectively [emergency room visits (US$39.15 vs US$2.70) and hospitalization (US$86.30 vs US$12.88)], per patient over 6 months. The costs with medications in the last month for patients with mild, moderate and severe asthma were US$1.60, 9.60, and 25.00 in the uncontrolled patients, respectively, and US$6.50, 19.00 and 49.00 in the controlled patients. In view of the small proportion of uncontrolled subjects receiving regular maintenance medication (22.2%) and their lack of resources, providing free medication for uncontrolled patients might be a cost-effective strategy for the public health system.